Inconveniences of Studying During a Pandemic - a Case Study - Mirosław Zalech; Lech Jaczynowski (Jan Długosz University in Częstochowa, 2020)
Introduction: The presented work is an attempt at diagnosing how much the restrictions connected with the COVID-19 pandemic have changed the lifestyle of students of the Faculty of Physical Education and Health (the University of Physical Education in Warsaw, the Branch in Biała Podlaska) and which inconveniences hindering normal studying are the most painful for them. Material and methods: The study included students of the aforementioned Faculty participating in classes dedicated to decision-making techniques as a part of subjects connected with the theory of organization and management. After those classes they worked out at home their answers referring to issues occurring within the following techniques: 1) the Daily Time Budget, 2) the Brainstorming, 3) the Fishbone Diagram, 4) the Borda-Kendall Method. The results were analysed with the "Statistica" computing package (13.3 version). The significance of intergroup differences (between students of different fields and men and women) was analysed with the χ². Results: It has been found out that there was a significant increase in the time devoted to self-study, watching the Internet and TV, homework. There were no classes in university premises as well as a decrease in social contacts. Among the factors that made studying more difficult, the lack of practical classes was ranked first, Internet problems second, and additional household chores came third. Conclusions: What turned out the most significant among inconveniences of online studies during the pandemic was limitation - or just lack - of practical classes, what is a problem requiring considerations and a systemic solution.